2013
DOI: 10.1161/hypertensionaha.113.00801
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Application of Recently Discovered Brain Mechanisms Involved in Hypertension

Abstract: A ccumulating evidence indicates that central activation of the sympathetic nervous system plays an important role in hypertension. [1][2][3][4][5][6][7][8] The aim of this review is to inform clinicians about the involvement of brain mechanisms in clinical hypertension and the applicability of recent findings to clinical practice. Clinicians, particularly cardiologists and nephrologists, are now initiating clinical treatment of hypertension that targets the sympathetic nervous system using novel techniques, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 120 publications
(219 reference statements)
0
24
0
Order By: Relevance
“…2012; Hirooka et al. 2013). Our recent studies also demonstrated that sympathoinhibition attenuated the LV dysfunction independently of blood pressure reduction in rats with hypertensive heart failure (Honda et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; Hirooka et al. 2013). Our recent studies also demonstrated that sympathoinhibition attenuated the LV dysfunction independently of blood pressure reduction in rats with hypertensive heart failure (Honda et al.…”
Section: Discussionmentioning
confidence: 99%
“…2009; Esler 2010; Malpas 2010; Hirooka et al. 2013; Florea and Cohn 2014). Although the sympathetic activity is modulated and controlled by brain, the mechanism by which brain senses the condition of heart failure from the body and leads to sympathoexcitaion have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanisms inducing the reduction in NO, bioavailability or impairment NO-mediated vasodilation in hypertension are not entirely understood, supportive evidence from experimental models is indicative of a bidirectional interaction between NO and SNS in modulating BP levels [61]. Accordingly, central production of oxidative stress in autonomic brain regions, particularly in the RVLM, increases central sympathetic activation thereby triggering BP elevation [64]. In this context, a better understanding of brain mechanisms linking oxidative stress to human neurogenic hypertension may help to implement novel therapies for drug-RH.…”
Section: Role Of Oxidative Stress In Central Brainstemmentioning
confidence: 99%
“…A wealth of information regarding the neuronal mechanisms that contribute to obesity-associated hypertension and sympathetic overdrive have been gathered in recent years (31). In particular, the brain melanocortinergic system has emerged as a crucial molecular pathway in the development of hypertension and other cardiovascular disorders in human obesity.…”
Section: Brain Mechanismsmentioning
confidence: 99%